1989
DOI: 10.1159/000469076
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Output Modulation of Alanine Aminopeptidase, γ-Glutamyl Transpeptidase and N-Acetyl-ß-D-Glucosaminidase by Castration and Testosterone in Male Normal Rat

Abstract: The urinary excretion of alanine aminopeptidase (AAP), γ-glutamyl transpeptidase (γ-GT) and of N-acetyl-ß-D-glucosami n idase (NAG) was studies in normal and castrated rats receiving either testosterone for 5 post-operative weeks or no hormone. In castrated rats the urinary output of AAP and γ-GT was significantly lower than in sham control or in castrated rats receiving testosterone. In addition, an excess of exogenously given testosterone had no effect on enzymuria of normal rats. The urinary excretion of NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…10-A). It was reported that urinary excretions of γGTP and alanine aminopeptidase, one of the enzymes localized at the BBM (Kettmann et al, 1992), were higher in male rats compared to female rats and castrated male rats (Grötsch et al, 1985;Girolami et al, 1989). Our results were consistent with their reports and suggested testosterone could increase in urinary excretions of enzymes localized at the BBM.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…10-A). It was reported that urinary excretions of γGTP and alanine aminopeptidase, one of the enzymes localized at the BBM (Kettmann et al, 1992), were higher in male rats compared to female rats and castrated male rats (Grötsch et al, 1985;Girolami et al, 1989). Our results were consistent with their reports and suggested testosterone could increase in urinary excretions of enzymes localized at the BBM.…”
Section: Discussionsupporting
confidence: 92%
“…The urinary NAG excretion levels varied little between the male and female animals and between the sham-operated and castrated animals in this study, corresponding with several literatures (Grötsch et al, 1985;Girolami et al, 1989;Pinches et al, 2012;Gautier et al, 2014). These consistent facts indicate that the sex hormones might have scarce effect on the urinary excretion level of NAG.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…875406). as recently reported [15]. One unit of activity corresponds to the release of 1 umol of product/min.…”
Section: Biochemical Assayssupporting
confidence: 63%